Maternal vitamin D status and its associated environmental factors: a cross-sectional study - Woon, Fui Chee; Aji, Arif Sabta; Lipoeto, Nur Indrawaty; Chin, Yit Siew (Jimma University, 2022)
Background: Vitamin D deficiency is common among women during pregnancy. This study aims to determine the prevalence of vitamin D deficiency and their shared modifiable environmental factors among pregnant women in Indonesia and Malaysia.METHODS: Blood samples of 844 third-trimester pregnant women (Indonesians: 311; Malaysians: 533) were collected to determine their serum 25(OH) D levels. Information on sun exposure and sun protection behaviours were obtained through face-to-face interviews. Dietary vitamin D intake was assessed by using a semi-quantitative food frequency questionnaire.Results: The prevalence of vitamin D deficiency (<30 nmol/L) among Indonesian and Malaysian pregnant women were 42.4% and 72.0%, respectively. Percentage of exposed body surface area was inversely associated with vitamin D deficiency among Indonesian pregnant women (OR = 0.21, 95% CI = 0.09-0.48). Among Malaysian pregnant women, higher intakes of dietary vitamin D were associated with lower risk of vitamin D deficiency (OR = 0.48, 95% CI = 0.29-0.81). Analysis of the combined cohorts revealed a lower risk of vitamin D deficiency among pregnant women who had a daily intake of at least 15 mcg vitamin D (OR = 0.58, 95% CI = 0.38-0.88) and exposure of more than 27% body surface area to the sunlight (OR = 0.30, 95% CI = 0.16-0.60).Conclusion: Despite abundant sunshine, vitamin D deficiency is prevalent among pregnant women in tropical countries. The present study suggests that nutrition education on vitamin D intake and sun exposure during pregnancy is necessary for primary prevention of vitamin D deficiency in pregnant women living in the tropical countries.